2019
DOI: 10.5430/ijhe.v9n1p1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Good University Governance and Student Satisfaction

Abstract: The purpose of this paper is to examine the relationship of good university governance, teaching quality of lecturers and student satisfaction. It also aims to examine the effect of learning facilities on good university governance and student satisfaction. 361 students of the Faculty of Economics, Semarang State University, were involved in this study using proportionate random sampling. Then, to gather the data, a questionnaire was distributed, and the data were analyzed by applying SEM-PLS. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 22 publications
(40 reference statements)
1
24
0
7
Order By: Relevance
“…As a result, satisfaction can be described as an experience of receiving expected results. In related research, satisfaction is often portrayed as the positive difference between the perceived importance and the perceived performance of an attribute or action [20]. In other words, satisfaction refers to the satisfaction or dissatisfaction experienced as a result of contrasting perceived results to expectations [18], [19].…”
Section: Defining Students Satisfactionmentioning
confidence: 99%
“…As a result, satisfaction can be described as an experience of receiving expected results. In related research, satisfaction is often portrayed as the positive difference between the perceived importance and the perceived performance of an attribute or action [20]. In other words, satisfaction refers to the satisfaction or dissatisfaction experienced as a result of contrasting perceived results to expectations [18], [19].…”
Section: Defining Students Satisfactionmentioning
confidence: 99%
“…As a result, satisfaction can be described as an experience of receiving expected results. In related research, satisfaction is often portrayed as the positive difference between the perceived importance and the perceived performance of an attribute or action (Muhsin et al, 2020). In other words, satisfaction refers to the satisfaction or dissatisfaction experienced as a result of contrasting perceived results to expectations (Suikkanen, 2011;Padula, 2015).…”
Section: Defining Students Satisfactionmentioning
confidence: 99%
“…The measurement of a student's educational experiences leads to a short-term disposition of satisfaction. It is the product and effect of an educational system and is a positive indicator of student loyalty (Weerasinghe & Fernando, 2017;Muhsin et al, 2020). In conclusion, student satisfaction can be understood as a function of the relative level of experiences and perceived performance concerning educational services during the study period (Suikkanen, 2011;Padula, 2015;Weerasinghe & Fernando, 2017).…”
Section: Defining Students Satisfactionmentioning
confidence: 99%
“…Osman and Saputra (2019) explained that the teaching method used by lecturers can be seen as an indicator of program quality in which it has a significant effect on student satisfaction. Recently, Muhsin et al (2020) also examined the connection between university governance, teaching quality of university lecturers and students' satisfaction. The study revealed that teaching quality of lecturers, learning facilities and good university governance had a positive and significant impact on students' satisfaction.…”
Section: Students' Satisfaction Of Educational Servicesmentioning
confidence: 99%